Association of Hepatitis C Virus Infection With CD4/CD8 Ratio in HIV-Positive Women. (1st June 2016) - Kuniholm, Mark H.; O'Brien, Thomas R.; Prokunina-Olsson, Ludmila; Augenbraun, Michael; Plankey, Michael; Karim, Roksana; Sarkar, Monika; French, Audrey L.; Pierce, Chris; Strickler, Howard D.; Anastos, Kathryn
Abstract : Background: Recent studies reported that the CD4/CD8 T-cell ratio is inversely associated with biomarkers traditionally used to measure immune activation and systemic inflammation in highly active antiretroviral therapy–treated HIV-infected (HIV+) patients. The relation of hepatitis C virus (HCV) coinfection with the CD4/CD8 ratio in HIV+ patients is unknown. Methods: We examined 50, 201 CD4/CD8 ratios measured over 20 years in 3 groups of HIV+ women enrolled in the Women's Interagency HIV Study: HCV antibody negative (n = 1734), cleared HCV (n = 231), and chronic HCV (n = 751) in multivariate models. IFNL4 -ΔG genotype and HCV viral load were also considered. Results: Compared with HCV antibody negative status, chronic HCV infection was associated with lower CD4/CD8 ratios when HIV viral load was suppressed to the lower limit of quantification (β = −0.08; P = 0.002). Cleared HCV (β = −0.10; P = 0.0009), but not IFNL4 -ΔG genotype or HCV viral load, was also associated with lower CD4/CD8 ratios when HIV viral load was suppressed to the lower limit of quantification. Conclusions: The association of HCV coinfection with CD4/CD8 ratio is consistent with previously observed associations of HCV coinfection with biomarkers traditionally used to measure immune activation and systemic inflammation in HIV+ patients. These data provide additional support for the use of CD4/CD8 ratio for routine monitoring of immune activation and inflammation in HIV+ patients, including those with HIV/HCV coinfection; however, the unexpected association between cleared HCV and lower CD4/CD8 ratio requires additional study. Abstract : Supplemental Digital Content is Available in the Text.